3D-QSAR CoMFA/CoMSIA Studies, to Design New VEGFR-2 Inhibitors - Batouche, S.; Gheid, A. (Asian Journal of Chemistry, 2010)
The vascular endothelial growth factor receptor 2 (VEGFR-2/KDR) is the target of current interest of anticancer drug research. Several classes of ligands have been studied as potential inhibitors against protein tyrosine kinases (PTK). To explore the relationships between the structure of the ligands and their inhibitory activity, 3D-QSAR analysis using CoMFA and CoMSIA techniques were performed on a series of 45 compounds. In this study we used three kinds of tyrosine kinase inhibitors with observable structural diversity in order to construct a universal 3D-QSAR model able to provide more useful information about their inhibitory mechanism. The binding conformation of these compounds was determined by using docking and alignment procedure. Based on their active conformation and their alignments, two highly predictive models were derived, CoMFA model (q2 = 0.620, r2 = 0.985) and CoMSIA model combined hydrophobic, hydrogen-bond donor and hydrogen-bond acceptor (q2 = 0.665, r2 = 0.960), both models were validated by a test set of 8 compounds producing very good predictive r2 values of 0.840 and 0.810, respectively. The CoMFA and CoMSIA contour maps were used to analyze the contribution of physicochemical properties on the activity of the inhibitors. The best models were used to design a new tyrosine kinase inhibitor with enhanced activity.